Kelayakan Finansial Usaha Penangkapan Ikan di Pantai Trisik, Kecamatan Galur, Kabupaten Kulon Progo - Sinung Rustijarno (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The research was done from June to August 2004 by cencus to all fishermen. This study was conducted in Trisik Coast, Galur Subdistrict, Kulon Progo District.The purpose of this research was to obtain the financial analysis of fishing effort in this area. The results showed that the fishing in Trisisik coast was feasible indicated by the Net Present Value (NPV) have positive value (Rp 21.439.196,-), Net B/C rasio (1,85) and Internal Rate of Return (IRR) (16,43%).